Pesan Moral dan Spiritual pada Nasyid Firru Ilallah Karya KH Hasan Abdullah Sahal (Kajian Semiotika Roland Barthes): Moral and Spiritual Messages in Nasyid Firru Ilallah by KH Hasan Abdullah Sahal (Roland Barthes' Semiotic Study) - Farouq Azra Ar Ridha; Cahya Buana; Rizqi Handayani; Minatur Rakhim; Siti Sa’adah (Information Technology and Science(ITScience), 2026)
This study aims to uncover the moral and spiritual meanings contained in Hasan Abdullah Sahal's nasyid Firru Ilallah using Roland Barthes's semiotic approach. This work was chosen because it implies strong da'wah values and presents a profound Islamic reflection through a combination of lyrics, tunes, and meaningful musical symbols. The nasyid not only functions as a medium for religious entertainment, but also as a means of conveying a moral message that directs humans to return to God and realize the true nature of life. The research method used is descriptive qualitative with a two-stage semiotic analysis according to Roland Barthes, namely denotative, connotative, and mythical meanings. The primary data in this study are nasyid lyric texts that are analyzed based on the structure of signs and the context of the meanings that appear in them. The results show that at the denotative level, the lyrics depict a call to return to God through an awareness of human sin, weakness, and limitations. At the connotative level, the nasyid presents a moral message about the importance of repentance, humility, and recognition of human dependence on God. Meanwhile, at the mythical level, a construction of spiritual values is found that emphasizes the concept of human nature and the spiritual journey toward the perfection of faith. Overall, the nasyid Firru Ilallah is not only a work of religious art but also serves as an effective medium for preaching, awakening moral, spiritual, and Islamic values in its listeners.